Amino acid metabolism and Hepatic Encephalopathy - Arora, Kirti (Innovative Research Thoughts, 2017)
Liver, the biochemical center on body with its abnormality invites myriad of complications along. Hepatic encephalopathy (HE) is out amongst various clinical symptoms of failure of liver, characterized by simple to complex abnormalities in case of hepatic insufficiency. The neuropsychiatric disorder has wide ranged clinical manifestations ranging from mood alterations to coma in acute cases. Keeping such wide manifestations in view, on the basis of west haven criteria, HE is categorized into five types: